Use of coconut fiber for particle enlargement of particulate matter in diesel exhaust - Gerente, Noel S.; Peralta, Genandrialine L.; Schnitzlein, Michael G.
As an alternative system to reduce particulate matter in the exhaust of older diesel engine, a post-muffler device is proposed that initially enlarges the ultra-fine diesel particulate matter in the exhaust so that the formed agglomerates can quantitatively be separated from the exhaust by subsequent cyclone type equipment. This study focuses on the problem of agglomeration of ultra-fine PM using a renewable fiber matrix. It is a feasibility study to use coir fiber matrix to induce significant particle coagulation to sizes well above 1 um. A housing was designed and fabricated with an approximate matrix volume of 13 liters which corresponded to 200-400 layers of coconut fiber in flow direction. A standardized glass filter was used to capture the particle fraction PM 2.5 out of the exhaust with a custom-made dilution channel. The study shows significant deposition and agglomeration of particulate matter from diesel exhaust. The obtained results support qualitatively the theoretically derived operating principle of the device. An outline is given for subsequent work to quantitatively evaluate the system and to adapt the equipment design for everyday use in public transport in the Philippines.
Keywords: Coir -- Diesel particulate filters